UPAYA GURU DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS XI KRIYA KREATIF BATIK DAN TEKSTIL DI SMK N 1 KALASAN - putri, ariana (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2025)
The background of the problem is that students have difficulty finding inspiration to complete assignments, are late in submitting assignments, and look unenthusiastic when studying. The purpose of the study was to find out what efforts teachers make to improve students' learning motivation. The type of research is descriptive qualitative. Data collection methods include: observation, interviews, and documentation. Data validity is carried out using triangulation techniques. The research procedure goes through the following stages: data collection, data reduction, data presentation, and conclusions. The results of the study are: (1) students gain an understanding of the learning process by understanding the goals and benefits of learning (2) students gain self-awareness of learning (3) teachers provide gentle touches as a motivator for students' enthusiasm (4) teachers give gifts as a form of appreciation (5) teachers give praise and awards as a form of appreciation (6) teachers create a healthy competitive learning climate in the classroom (7) teachers do not inform students of their learning achievements (8) teachers use multimedia when teaching (9) teachers use multi-methods when teaching.   Keywords: Teacher Effort, Learning Motivation, Creative Batik Crafts